Dynamic cyclic bending, kinetic to strain energy, deceleration systems - Burger, N.D.L (Nicolaas Daniel Lombard) (University of Pretoria, 2013)
Dissertation (M Eng (Mechanical Engineering))--University of Pretoria, 2007.